Intercropping Lentil with Mukhikachu (Collocasia Esculenta) at Different Planting Systems - Alom, MS; Islam, MN; Nag, BL; Howlader, MM; Hossain, MA (Bangladesh Journal of Agricultural Research, 2012)
The experiment was conducted at the Regional Agricultural Research Station, BARI, Jessore during consecutive two years (2007-08 and 2008-09) to find out the comparative performance of different intercropped lentil with Mukhikachu for getting higher yield and economic return. Five treatments comprised of T1= Sole lentil (30 cm apart continuous seeding), T2 = Sole mukhikachu [(double row) = 20 cm/55/20 cm x 45 cm], T3= Mukhikachu (double row) + 1 row of lentil 30 cm apart (33% seeding ratio) between 2 double row of mukhikachu, T4 = Mukhikachu (double row) + 2 rows of lentil 30 cm apart (66%) between 2 double row of mukhikachu and T5= Mukhikachu (double row) + lentil broadcast (100%). Intercropping systems did not affect the rhizome yield of mukhikachu significantly but affected the seed yield of lentil. Lentil and mukhikachu equivalent yield were the highest (5.87 in 2007-08 and 6.09 t/ha in 2008-09, and 27.24 in 2007-08 and 30.45 t/ha in 2008-09, respectively) in treatment T4. This treatment also gave the highest LER (1.63 in 2007-08 and 1.54 in 2008-09), net return (Tk. 290508 in 2007-08 and Tk. 368900/ha in 2008-09) with BCR of 4.19 in 2007-08 and 4.88 in 2008-09, respectively. It reveals that lentil could be grown easily in double row system of Mukhikachu without hampering yield of Mukhikachu with higher benefit and also enhanced lentil production in the area. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11757 Bangladesh J. Agril. Res. 36(4): 669-676, December 2011